DEVELOPMENT OF SHARED-TYPE INTEGRATED SCIENCE E-MODULE BASED ON PROBLEM-BASED LEARNING ON THE TOPIC OF ENVIRONMENTAL POLLUTION - Aulira, Intan; Sari, Monica Prima (Universe, 2024)
The purpose of this research is to produce the development Of Shared-Type Integrated Science E-Module Based On Problem-Based Learning On The Topic Of Environmental Pollution for a student junior high schools. This research uses the research and development (R&D) with a 4-D models. The development of this 4-D model has 4 stage of development namely : define, design, develop, and desseminate. However, this research was carried out until the develop stage only. This research data is calculated using the Formula Moment Kappa (k) to analyze the results of the validity and practicality of e-module test developed. E-module validity test results obtained an average value of 0,92 with a very valid category. The results of the E-module practicality test conducted on teachers and students were 0,93 and 0,86 with very practical categories, respectively. The conclusion of this study is that the development Of Shared-Type Integrated Science E -Module Based On Problem Based Learning On The Topic Of Environmental Pollution for a student junior high schools is valid and practical.